DD-003 Analysis of the use of automated medicines dispensing cabinets without electronically assisted prescribing. (24th March 2015) - Izquierdo Acosta, L; Viyuela, MD; Benito, V; Oca, B; Alamo, O; Chico, J; Martinez, R; Hermida, C
Abstract : Background: Automated medicines dispensing cabinets (ADCs) have recently been introduced in all areas of a tertiary hospital. Purpose: To analyse the changes made by nurses when using the ADCs to the prescriptions made by physicians without electronically assisted prescribing. Material and methods: A retrospective observational study was made looking over the computerised clinical histories of inpatients from the Internal Medicine and Traumatology wards. These were compared to the records of drug withdrawals, analysing consumption per patient, classes and length of treatment. Consumption per patient was the net amount, taking into account withdrawals, returns to stock and drawer returns. Results: 22 patients were included, 15 belonged to Traumatology and 7 to Internal Medicine. The mean hospital stays were 13.9 and 7.6 days, respectively. 145 drugs were prescribed in Traumatology (9.6 per patient) and 117 in the Internal Medicine Service (16.7 per patient). The study was conducted on the drugs contained in the ADCs (124 and 83). The rest belonged to restricted drugs and those not included in the hospital guidelines. The consumption per patient and dose were changed in 40.32% of the cases in Traumatology and in 39.7% of cases in Internal Medicine. Moreover, in Traumatology a mean of 2.46 medicines per patient were taken from the cabinets without having being prescribed in the clinical history (4.3 in the case of Internal Medicine). In Internal Medicine (though not in Traumatology) we found that on 67 occasions the quantities of drugs withdrawn from the ADCs exceeded the corresponding quantities administered. Conclusion: The improper use of the ADCs calls into question the correct administration of the drug treatment to the patients. So as electronically assisted prescribing is being phased in throughout the hospital, it will be necessary to train the nursing staff to withdraw only the medicine prescribed per patient per shift in order to improve safety and to prevent drug errors. References and/or acknowledgements: None No conflict of interest.